Human reliability analysis: A critique and review for managers - French, Simon; Bedford, Tim; Pollard, Simon J. T.; Soane, Emma (Elsevier Science B.V., Amsterdam., 2011)
In running our increasingly complex business systems, formal risk analyses and risk management techniques are becoming a more important part of a manager's tool-kit. Moreover, it is also becoming apparent that human behaviour is often a root or significant contributing cause of system failure. This latter observation is not novel; for more than 30 years it has been recognised that the role of human operations in safety critical systems is so important that they should be explicitly modelled as part of the risk assessment of plant operations. This has led to the development of a range of methods under the general heading of human reliability analysis (HRA) to account for the effects of human error in risk and reliability analysis. The modelling approaches used in HRA, however, tend to be focussed on easily describable sequential, generally low-level tasks, which are not the main source of systemic errors. Moreover, they focus on errors rather than the effects of all forms of human behaviour. In this paper we review and discuss HRA methodologies, arguing that there is a need for considerable further research and development before they meet the needs of modern risk and reliability analyses and are able to provide managers with the guidance they need to manage complex systems safely. We provide some suggestions for how work in this area should develop.